Conflict probability evaluation taking into account the dynamics and correlation of aircraft flight process - Васильєв, В.М. (Proceedings of National Aviation University (archive), 2004)
The probability method of conflict detection for collision avoidance systems is offered enabling to take into account the features of stochastic dynamics of aircraft flight process and correlation of a trajectory with time. The general approach to a solution of a problem is presented and the analytical solution on a concrete example is demonstrated.